Uso da música para alunos com Transtorno do Espectro do Autismo na sala de recursos multifuncionais: revisão narrativa - Rodrigues, Rhayane Fernandes dos Santos (Universidade Federal de São Carlos, 2022)
This study had as its principle the bibliographic review of works related to the use of music for people diagnosed with Autism Spectrum Disorder, by teachers in the multifunctional resource room. Thus, we sought to analyze the literature and discuss the narratives of what has been shown in research relevant to the subject. Of a bibliographic nature, the work was developed from the search in the databases of the Scientific Electronic Library Online (SciELO), CAPES Periodicals Portal and the Brazilian Digital Library of Theses and Dissertations (BDTD). Four studies were found that address the theme Autism Spectrum Disorder and music, in addition to listing the main benefits of its use, however, no research was found that related the use of music in multifunctional resource rooms. Thus, the findings show the most diverse gains in the development and behavior of individuals with Autism Spectrum Disorder when methodologies are implemented that use music as a form of repertoire promotion, however, the lack of research that studies the performance of professionals in multifunctional resource rooms that appropriate music in their approach and intervention. Thus, there is a need for more research in this area.
Use of music for students with Autism Spectrum Disorder in the multifunctional resource room: narrative review
Keywords: Educação Especial; Transtorno do Espectro do Autismo; Música; Special Education; Autism Spectrum Disorder; Music; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO